Peningkatan Kesejahteraan Psikologis pada Penderita Diabetes Mellitus Tipe 2 dengan Menggunakan Group Positive Psychotherapy - Rima Christine Sujana; Hepi Wahyuningsih; Qurotul Uyun (Universitas Islam Indonesia, 2015)
This study aims to determine the improvement of psychological well-being in patients with type 2 diabetes mellitus using group positive psychotherapy. Subjects in this study were 12 patients with type 2 diabetes mellitus (men and women) between the ages of 47-64 years, and divided into two groups, namely the experimental group and the control group. This study uses a scale of psychological well-being (22-item), which refers to the dimensions of psychological well-being by Ryff (1989). Quantitative data analysis using parametric analysis techniques one-way repeated measures anova to see the differences in psychological well-being of the experimental group after the subject therapy. The results show that there are differences in psychological well-being in the experimental group after therapy, with a value of Wilks' Lambda = 0.153, p = 0.00 (p <0.01). The conclusion from this study that the group positive psychotherapy can improve psychological well-being of people with type 2 diabetes mellitus. Key words: Group Positive Psychotherapy, Psychological Well Being, Type 2 Diabetes Mellitus